IDENTIFIKASI KELESTARIAN KAWASAN KOTA LAMA MELALUI PROTEKSI BANGUNAN CAGAR BUDAYA OLEH PEMERINTAH KOTA SURABAYA - Dimas Widya Putra (Jurnal Pengembangan Kota, 2016)
Surabaya old town district was the historical evidence of the Dutch Government in Colonial era, The center of the Dutch Administration located in Old Town, meanwhile Old Town District was the whiteness of Dutch defeat. Many buildings built by the Dutch in Colonial era are still conserved. Surabaya has strategy and policy through Tourism and Culture Department to conserve these buildings to be a landmark and legacy of city, this study addresses to evaluate the policy associated with the protection of heritage buildings, to examine the policy and to sum up the findings associated to conservation theory. This research uses the character appraisal, quantitative and qualitative. The result found are several buildings have been protected by the policy, however, there is a segment made so many facade changes and several well ornamented buildings. The conclusion obtained that the cultural heritage building policy can be nicely applied, especially to the historical value buildings. The Government gives a tolerance to renovate the buildings having less strong historical value.